Learning Innovation of Qibla Direction with Mobile-Based App by Adapting Computational Thinking - Fajar Fathurahman (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
This research was conducted to obtain the results of the development of Learning to Determine Qibla Direction with Computational Thinking Adaptation using Mobile-Based Applications. The researcher used mixed methods with a sequential exploratory research design that takes two stages (qualitative-quantitative). The R & D stage used 5 (five) steps of the ADDIE method, namely Analysis, Design, Development, Implementation and Evaluation. This research was conducted at the office of the Ministry of Religion of the Thousand Islands Regency, with the result that the learning innovations carried out were appropriate and met expectations. The learning process for training participants and in practice its application was easier and more affordable. The Qibla direction training used in this mobile-based application was applied with a learning pattern that adapts computational thinking skills, which were arranged in four phases, namely: Elaboration, Determination, Calculation, and Evaluation. This learning innovation shows that it can improve participants' understanding of the concept of calculating Qibla Direction which was applied integratively between religion, science and technology as a coherent knowledge. Keywords: Mobile-Based App, Learning Innovation, Adapting Computational Thinking